Condicionamento fisiológico de sementes de Coffea arabica L. - Frota, Giovana Janini (2021)
Coffee is one of the most important agricultural products traded in the world and in Brazil, being the second most important item in the international trade of commodities, behind only oil. The use of of high quality seeds is a crucial factor for obtaining more vigorous coffee seedlings under field conditions and, consequently, for the formation of healthy and productive crops. Thus, the storage of coffee seeds is a great challenge for seed producers, since Coffea arabica L. seeds are classified as intermediate, that is, they have low longevity. Another factor that interferes with the quality of coffee seeds during storage is the production of free radicals, which are involved in several aspects of seed physiology. Its generation occurs during seed desiccation, germination and aging, which can lead to oxidative stress and cell damage, resulting in deterioration. However, the cells have an antioxidant defense enzyme system that captures free radicals and participates in the survival of the seeds. Detoxification mechanisms play a key role in completing seed germination and seed storage. Physiological conditioning is an alternative to improve the performance of seeds that present germination and vigor problems, as is the case of stored coffee seeds, since this technique has the advantages of increasing speed and uniformity in seedling emergence and seed tolerance to adverse environmental conditions and physiological stresses that cause an increase in free radical production. Therefore, the research was proposed in order to evaluate the effect of physiological conditioning on Coffea arabica L. seeds subjected to different conditioning solutions, through evaluations of physiological characteristics associated with enzymatic activity.